Community-Acquired Acute Kidney Injury Induced By Drugs In Older Patients: A Multifactorial Event - Robert L (Dove Medical Press, 2019)
Laurine Robert,1 Grégoire Ficheur,2 Sophie Gautier,3 Alexandre Servais,1 Michel Luyckx,4 Julien Soula,1 Bertrand Decaudin,5 François Glowacki,6 François Puisieux,1 Emmanuel Chazard,2 Jean-Baptiste Beuscart1 1Univ. Lille, CHU Lille, EA2694, Lille, F-59000, France; 2Univ. Lille, CHU Lille, EA2694, Public Health Department, Lille, F-59000, France; 3Univ. Lille, CHU Lille, UMR 1171, Department of Pharmacology, Lille, F-59000, France; 4Univ. Lille, EA7365, F-59000 Lille, CH Denain, Department of Pharmacy, Denain, F-59220, France; 5Univ. Lille, CHU Lille, EA7365, Department of Pharmacy, Lille, F-59000, France; 6Univ. Lille, CHU Lille, EA4483 IMPECS, Department of Nephrology, Lille, F-59000, FranceCorrespondence: Laurine RobertCERIM – EA 2694, Faculté de Médecine - Pôle Recherche, 1 Place de Verdun, Lille Cedex 59045 FranceEmail laurine.robert.etu@univ-lille.frPurpose: Community-acquired acute kidney injury (CA-AKI) is a frequent and severe adverse drug reaction (ADR) among older patients. The combination of drugs and other CA-AKI risk factors was barely evaluated. The objectives of our study were to both accurately identify CA-AKI induced by drugs in older patients, and to describe their combination with other risk factors.Patients and methods: We conducted a retrospective, single-center study in a general hospital over a two-year period. An automated detection identified CA-AKI according to KDIGO criteria, amongst 4,767 eligible inpatient stays among patients aged 75 years or older. Two independent experts reviewed all CA-AKI events to adjudicate drug involvement (Naranjo scale), identify inappropriate prescriptions (STOPP criteria), evaluate avoidability (Hallas criteria) and identify combined risk factors.Results: An expert review confirmed 713 CA-AKI (15.0% of inpatient stays) and determined that 419 (58.8%) CA-AKI were induced by drugs. A multifactorial cause (i.e., at least one drug with a precipitating factor) was found in 63.2% of drug-induced CA-AKI. Most of the drug-induced events were avoidable (66.8%), mainly in relation to a multifactorial cause.Conclusion: Drug-induced CA-AKI were frequent, multifactorial events in hospitalized older patients and their prevention should focus on combinations with precipitating factors.Keywords: adverse drug reactions, elderly, prevention, acute kidney injury